Evaluating Impact of Social Media Marketing, Celebrity Endorsement and E-WOM on Online Repurchase Intention with the Mediating Role of Perceived Usefulness - Liaqat, Ayesha (Pakistan Journal of Humanities and Social Sciences, 2023)
The purpose is to examine the impact of social media marketing, celebrity endorsement and e-wom on online repurchasing intentions with the mediating effect of perceived usefulness. In the continuous survey, assembles made from existing hypotheses, produce hypotheses, embrace frameworks for data arrangement and perform tests to exhibit the proposed hypothesis. The apparel industry is the main unit of analysis throughout the investigation of these variables. Our research is quantitative and also adopts a deductive approach. As a technique for advancing the large name stalwart's things and building up the relationship with the lovers, live trade gatherings (or live transmissions) between the genius force to be reckoned with and the allies can be set up on Instagram. These events could enable the Whiz amazing powerhouse and their allies to interface, which could augment thing bargains(Wahab et al., 2022). Speculatively, this study has shown that the development of disposition parts mental profound approach to acting may not commonly be dependable as a result of explicit factors. In this model, clients' viewpoints and objectives to buy things from enormous name stalwart brands are more grounded when they feel related to the celebrities' lives, triumphs, frustrations, wants, etc, as well as when they have solid areas for a bond with the celebrities, as affirmed by their super individual levels of celebrity love. Customers who show this commitment view themselves as the celebrity awe-inspiring phenomenon’s most noteworthy partners. When something enabling happens to them, they are especially excited about the notable awe-inspiring phenomenon. They could have a merry point of view toward a celebrity stalwart's achievement, for instance, when the celebrity force to be reckoned with gets or even think of them as their ideal accomplice. Along these lines, the buyers would wish to assist the hotshot with compelling to be dealt with's business attempts as undaunted disciples by buying things made by the large name. The survey's unessential revelations are more than likely achieved by the strong levels of respect and wonderment that a larger piece of the purchasers have for the celebrity forces to be reckoned with. This exploration is giving valuable data to the advertisers of Pakistan’s private sector universities in understanding consumers’ needs deeper in order to contribute to the growth of their business. The data is gathered through questionnaires. The data is aggregated through surveys. This specific framework and variables are only being used in Pakistan.